ANN-based predictive modelling of multiband absorption properties for eco-friendly microwave absorbers - Ahmad, Azizah (2026)
The rapid advancement of Industry 4.0 technologies and widespread adoption of 5G communication systems have heightened public concerns about the potential health risks associated with electromagnetic radiation. To mitigate these risks, eco-friendly microwave absorbers have emerged as a promising solution, effectively reducing radiation exposure. However, predicting the absorption performance remains challenging due to their complex and nonlinear interaction with electromagnetic waves. This research proposes a two-stage modelling approach to classify the absorption performance of eco-friendly single-slot pyramidal microwave absorbers.